2020
DOI: 10.1002/suco.202000433
|View full text |Cite
|
Sign up to set email alerts
|

Thermal damage and its controlling methods of high‐speed railway steam‐cured concrete: A review

Abstract: The steam curing technology is worldwide applied in the production of concrete prefabricated components, including the production of track slab and girder used for the high‐speed railway in China. However, the steam curing process at elevated temperature will often generate the heat damage on concrete and thus degrade the long‐term performance of the steam‐cured concrete prefabricated components. It is very important to deeply understand the mechanism of heat damage and thus to find effective method reducing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…By the way, the lowest open porosity/water absorption of HCM blended with LWFA and FA among four mixtures at 60 d indicates that the synergistic effect of them can substantially the surface microstructure of HCM. Actually, the improvement of surface property is meaningful to the engineering practice of heat-cured materials since they commonly encounter the issue of thermal damage, especially the surface [65][66][67]. A dense surface microstructure is beneficial to not only the strength but also the resistance to ion penetration.…”
Section: Pore Structurementioning
confidence: 99%
“…By the way, the lowest open porosity/water absorption of HCM blended with LWFA and FA among four mixtures at 60 d indicates that the synergistic effect of them can substantially the surface microstructure of HCM. Actually, the improvement of surface property is meaningful to the engineering practice of heat-cured materials since they commonly encounter the issue of thermal damage, especially the surface [65][66][67]. A dense surface microstructure is beneficial to not only the strength but also the resistance to ion penetration.…”
Section: Pore Structurementioning
confidence: 99%
“…Another main function of steam curing is to improve the productivity and efficiency of molds 30 . Nonetheless, previous studies on the thermal effects of steam curing illustrated that the accelerated hydration of cementing material could cause the volume expansion, the surface micro‐crack, the crystallization of hydrates, and pore coarsening, 31–36 and thus resulted in the degradation in the long‐term durability of steam‐cured concrete 37 …”
Section: Introductionmentioning
confidence: 99%
“…SC shortens the demolding times and to increases productivity, which improves the economic efficiency. However, many studies have suggested that SC has some adverse effects on specimens, such as coarsening of pores [9,10], thermal damage leading to cracking [11,12], reduction of long-term performance [13], and reduction of durability performance [14]. In response to the advantages and disadvantages of SC, a new direct electrical curing (EC) [15] method has been discovered by research scholars .EC uses fresh specimens with low resistivity [16] to generate uniform Joule heat under the current to accelerate the hydration of cement and enhance early mechanical properties.…”
Section: Introductionmentioning
confidence: 99%